2017
DOI: 10.3390/atmos8070124
|View full text |Cite
|
Sign up to set email alerts
|

Street-Level Ventilation in Hypothetical Urban Areas

Abstract: Street-level ventilation is often weakened by the surrounding high-rise buildings. A thorough understanding of the flows and turbulence over urban areas assists in improving urban air quality as well as effectuating environmental management. In this paper, reduced-scale physical modeling in a wind tunnel is employed to examine the dynamics in hypothetical urban areas in the form of identical surface-mounted ribs in crossflows (two-dimensional scenarios) to enrich our fundamental understanding of the street-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 70 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…The urban built intensity determines the ventilation efficiency of the ventilation path [ 35 , 36 ]. As a morphological characteristic of the built environment, the urban built intensity has an obvious correlation with ventilation potential [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The urban built intensity determines the ventilation efficiency of the ventilation path [ 35 , 36 ]. As a morphological characteristic of the built environment, the urban built intensity has an obvious correlation with ventilation potential [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…But, the natural ventilation effect is greatly affected by external climate conditions (such as wind speed, wind direction, and temperature differences), and it is difficult to ensure a stable ventilation effect. To examine the dispersion patterns of pollutants in urban settings under natural ventilation, researchers' studies have focused on analyzing pollutant dispersion in street canyons through CFD simulations [5][6][7][8][9], wind/water tunnel experiments [2,[10][11][12], and field measurements [13][14][15]. The primary source of pollutant exposure within street canyons stems from vehicle emissions, which vary across vehicle models and emission levels under distinct driving conditions.…”
Section: Existing Research and Practical Applications Indicate That N...mentioning
confidence: 99%
“…Much effort has been done in recent years to analyze urban canopy flows by means of CFD, often using Reynolds-averaged NavierStokes (RANS) simulations of two-dimensional (2D) arrays of buildings. e interest of the scientific community for such a simplified building arrangement is justified by the fact that the 2D array can be considered as an archetype for more complex geometries [10][11][12][13]. Huang et al [14] carried out 2D simulations to investigate the effect of wedge-shaped roofs on the flow in an urban street canyon and found that they have significant influence on the vortex structure and pollutant distribution pattern.…”
Section: Introductionmentioning
confidence: 99%